Chlorhexidine-alcohol versus Povidone-Iodine-alcohol for surgical site antisepsis in caesarean section - Kesani, Vishnu Priya; Talasila, Sruthi; S. R., Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Caesarean section is one of the most common procedures performed. Recent studies found that surgical-site infection (SSI) was the most common healthcare-associated infection. Authors hypothesized that optimization of preoperative skin antisepsis may decrease postoperative infections. The objective was to establish the efficacy of chlorhexidine-based antiseptic protocol versus povidone-iodine protocol in reducing SSI for patients undergoing caesarean deliveries. Methods: This is a randomized prospective study conducted from April 2017 to September 2017 at a tertiary care center in India. Women who underwent caesarean sections were allocated into either group. Enrolled patients were randomly assigned to have the surgical site painted with chlorhexidine-alcohol preparation or painted with a solution of 10% povidone-iodine and then with surgical spirit. The outcomes were any SSI occurring within a week or during the 30 day follow up period of the surgery including any of: superficial or deep surgical site infection, or endometritis, according to Centers for Disease Control and Prevention definitions. Results: A total of 560 subjects (273 in the chlorhexidine group and 287 in the iodine group) qualified for the study. The number of surgical-site infection was significantly lower in the chlorhexidine group than in the iodine group (6.95% vs. 14.28%; P=0.005). Chlorhexidine–alcohol was significantly more protective than iodine-alcohol against both superficial incisional infections (5.49% vs. 10.10%, P=0.03) and deep incisional infections (1.46% vs. 4.18%, P=0.04). Conclusions: This study highlighted that Chlorhexidine-alcohol provided superior skin antisepsis in comparison to povidone iodine-alcohol.